2018
DOI: 10.1016/j.neuroimage.2018.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the topological organisation of beta oscillations in motor cortex using MEG

Abstract: The spatial topology of the human motor cortex has been well studied, particularly using functional Magnetic Resonance Imaging (fMRI) which allows spatial separation of haemodynamic responses arising from stimulation of different body parts, individual digits and even spatially separate areas of the same digit. However, the spatial organisation of electrophysiological responses, particularly neural oscillations (rhythmic changes in electrical potential across cellular assemblies) has been less well studied. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 74 publications
(84 reference statements)
0
25
0
Order By: Relevance
“…In fact, several neurological conditions have shown altered patterns of rhythmic beta activities. For instance, multiple sclerosis patients show abnormal beta rebound (Barratt et al, 2018 ). Alterations in beta activity are also observed in states, such as stroke (Rossiter et al, 2014 ) and Parkinson’s disease (Heida et al, 2014 ; Little and Brown, 2014 ; Dubbioso et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several neurological conditions have shown altered patterns of rhythmic beta activities. For instance, multiple sclerosis patients show abnormal beta rebound (Barratt et al, 2018 ). Alterations in beta activity are also observed in states, such as stroke (Rossiter et al, 2014 ) and Parkinson’s disease (Heida et al, 2014 ; Little and Brown, 2014 ; Dubbioso et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we opted to use separate spatial filters, rather than single spatial filter based on the M100 as used in previous studies [2,44,45]. This was based on recent work suggesting that beamformer weights should be optimised for specific data of interest [46].…”
Section: Source-level Spectral Powermentioning
confidence: 99%
“…Given the poor spatial resolution of EEG, perhaps the future should see a shift in focus towards other neuroimaging modalities more suited to the task. In 2018, using MEG, Barratt et al showed that oscillatory beta responses to moving an index and pinky finger of the same hand were spatially separable for participants wearing a head-cast [28]. There are various clinical obstacles to overcome when using MEG but this level of separability is enviable amongst EEG researchers.…”
Section: Discussionmentioning
confidence: 99%